1996
DOI: 10.2165/00002018-199614030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Tinnitus and Other Hearing Disorders

Abstract: Tinnitus and hearing loss, both reversible and irreversible, are associated both with acute intoxication and long term administration of a large range of drugs. The mechanism causing drug-induced ototoxicity is unclear, but may involve biochemical and consequent electrophysiological changes in the inner ear and eighth cranial nerve impulse transmission. Over 130 drugs and chemicals have been reported to be potentially ototoxic. The major classes are the aminoglycosides and other antimicrobials, anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0
6

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 116 publications
2
89
0
6
Order By: Relevance
“…Seligmann et al (1996) listed more than 130 drugs and chemicals reported to be potentially ototoxic, with the major classes of known ototoxic compounds being the aminoglycosides and other antimicrobials, anti-inflammatory agents, diuretics, antimalarial drugs, antineoplastic agents, and some topically administered agents. Most of these drugs were initially recognized as being ototoxic after anecdotal reports of hearing loss, tinnitus, or balance impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Seligmann et al (1996) listed more than 130 drugs and chemicals reported to be potentially ototoxic, with the major classes of known ototoxic compounds being the aminoglycosides and other antimicrobials, anti-inflammatory agents, diuretics, antimalarial drugs, antineoplastic agents, and some topically administered agents. Most of these drugs were initially recognized as being ototoxic after anecdotal reports of hearing loss, tinnitus, or balance impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Lormetazepam's 10-hour elimination half-life makes any withdrawal phenomenon between 2 drug administrations unlikely. An interesting element is the qualitative change in the hallucination with the introduction of amitriptyline, because tinnitus is reported by about 1% of patients receiving tricyclic antidepressants (11). The continued symptoms after the drugs were stopped could suggest that some undetected predisposing oto-neurologic factors facilitated the appearance of the hallucination François Curtin, MD, MPhil Charles Remund, MD Geneva, Switzerland…”
mentioning
confidence: 99%
“…These agents may damage the cochleae and may cause vertigo, tinnitus, and hearing loss. Ototoxicity due to cisplatin has been reported in 10%-70% of adults (6,7). In a study by Reddel et al (8), ototoxicity was detected in 72% of adult patients treated with cisplatin.…”
Section: Discussionmentioning
confidence: 99%